Advanced Analytics with R and Tableau - Stirrup, Jen (Packt Publishing Limited, 2017)
bLeverage the power of advanced analytics and predictive modeling in Tableau using the statistical powers of R/bh2About This Book/h2ulliA comprehensive guide that will bring out the creativity in you to visualize the results of complex calculations using Tableau and R/liliCombine Tableau analytics and visualization with the power of R using this step-by-step guide/liliWondering how R can be used with Tableau? This book is your one-stop solution./li/ulh2Who This Book Is For/h2This book will appeal to Tableau users who want to go beyond the Tableau interface and deploy the full potential of Tableau, by using R to perform advanced analytics with Tableau.A basic familiarity with R is useful but not compulsory, as the book will start off with concrete examples of R and will move quickly into more advanced spheres of analytics using online data sources to support hands-on learning.
Keywords: COMPUTERS / Data Visualization; COMPUTERS / Enterprise Applications / Business Intelligence Tools